Triticale: A General Overview of Its Use in Poultry Production - Gaviley, Olena; Katerynych, Oleg; Ionov, Igor; Dekhtiarova, Olena; Griffin, Darren; Romanov, Michael (My University, 2024)
Triticale is a valuable forage crop, it has both a number of advantages and many problems that require some study. Due to its high yield, high starch content, fullness and completeness of grain, modern varieties of triticale among cereal crops are an affordable and valuable feed in different regions of the world. The use of triticale in animal and poultry feeding is gradually increasing. This contributes to the expansion of the feed base, increasing the multicomponent nature of rations, and reducing competition for wheat. However, as evidenced by literature data, depending on the level of triticale in the diet, poultry productivity may change, increase or decrease, compared to wheat-based diets. Analysis of literature data on the norms of using triticale in animal and poultry feeding indicates the ambiguity of the results obtained. The difference in results may probably be associated with both the methods of conducting experiments and different varieties of triticale and the conditions of their cultivation in our country and in European countries. The use of additional feed additives is effective in some cases and has no effect in others. In addition, it should be noted that the effectiveness of triticale depends largely on the content of antinutrients in it. And in this regard, the data obtained in various experiments are also quite contradictory. Taking into account the prospects for the use of triticale in poultry farming and the expansion of its cultivation areas in Ukraine, it is relevant to develop and implement new methods for the effective use of high triticale content in compound feeds in feeding breeding chickens using: enzyme preparations for cereals, taking into account the characteristics of varieties and climatic conditions; production of triticale-soybean and triticale-sunflower extrudates; as well as by enriching the diet with critical amino acids. Тритикале є цінною кормовою культурою, воно має як ряд переваг так і безліч проблем, які потребують певного вивчення. Завдяки високій врожайності, високому вмісту крохмалю, виповненості і повновагості зерна сучасні сорти тритикале серед зернових культур тритикале є доступним і цінним кормовим засобом в різних регіонах світу. Застосування тритикале в годівлі тварин та птиці поступово збільшується. Це сприяє розширенню кормової бази, підвищенню багатокомпонентності раціонів, зниженню конкуренції за пшеницю. Проте, як свідчать літературні дані, залежно від рівня тритикале в раціоні продуктивність птиці може змінюватись, підвищуватись чи знижуватись, порівняно з раціонами на основі пшениці. Аналіз літературних даних щодо норм застосування тритикале в годівлі тварин та птиці свідчить про неоднозначність одержаних результатів. Різниця в результатах, певно, може бути пов’язана як з методиками проведення дослідів, так і різними сортами тритикале та умовами їх вирощування в нашій країні і в країнах Європи. Застосування додатково різних кормових добавок ефективне в одних випадках і не має ніякого впливу в інших. Крім того, слід зазначити, що ефективність використання тритикале значною мірою залежить від вмісту в ньому антипоживних речовин. І в цьому питанні одержані в різних дослідах дані також досить суперечливі. Приймаючи до уваги перспективність використання тритикале у птахівництві та розширення площ його культивування в Україні, актуальним є розроблення та впровадження нових способів ефективного використання високого вмісту тритикале у складі комбікормів в годівлі племінних курей за допомогою: ферментних препаратів для злакових, з урахуванням особливостей сортів і кліматичних умов; виготовлення тритикале-соєвого та тритикале-соняшникового екструдатів; а також шляхом збагачення раціону критичними амінокислотами.
Triticale: A General Overview of Its Use in Poultry Production / O.V. Gaviley, O. O. Katerynych, I. A. Ionov, О. О. Dekhtiarova, D. K. Griffin, M. N. Romanov // Encyclopedia, 2024. – № 4. – Р. 395–414.
Keywords: тритикале, сільськогосподарська птиця, курчата, амінокислоти, антипоживні речовини, ферментативна обробка, екструзія; triticale; poultry farming; feeds; chickens; amino acids; antinutrients; enzymatic treatment; extrudates